Development of a highly effective combination monoclonal antibody therapy against Herpes simplex virus - Seyfizadeh, Narges; Kalbermatter, David; Imhof, Thomas; Ries, Moritz; Müller, Christian; Jenner, Leonie; Blumenschein, Elisabeth; Yendrzheyevskiy, Alexandra; Grün, Frank; Moog, Kevin; Eckert, Daniel; Engel, Ronja; et al. (Journal of biomedical science, 2024)
Infections with Herpes simplex virus (HSV)-1 or -2 usually present as mild chronic recurrent disease, however in rare cases can result in life-threatening conditions with a large spectrum of pathology. Monoclonal antibody therapy has great potential especially to treat infections with virus resistant to standard therapies. HDIT101, a humanized IgG targeting HSV-1/2 gB was previously investigated in phase 2 clinical trials. The aim of this study was to develop a next-generation therapy by combining different antiviral monoclonal antibodies.
Veröffentlicht: 28 May 2024
Gesehen am 11.06.2025